2016
DOI: 10.1039/c6cc06006d
|View full text |Cite
|
Sign up to set email alerts
|

Microsecond resolution of cavitation bubble dynamics using a high-speed electrochemical impedance approach

Abstract: A new method to detect the uncompensated resistance, the capacitance and the Faradaic current at an electrode exposed to ultrasonic cavitation is presented. The method enables these parameters to be resolved with a 2 microsecond resolution and relies on the detection of the impedance of an electrode recorded as a function of time with a suitable AC excitation signal (here 500 kHz). Data obtained from an aluminium electrode, held under potentiostatic control, is used to illustrate the technique with particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The pump (Hailea HX8810, not shown in Figure 1) took electrolyte from the main reservoir (~2.5 dm 3 ) and pumped it through the jet after passing a loading port where sand was added to the flow system. The high-speed impedance system has been described in detail elsewhere [28].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pump (Hailea HX8810, not shown in Figure 1) took electrolyte from the main reservoir (~2.5 dm 3 ) and pumped it through the jet after passing a loading port where sand was added to the flow system. The high-speed impedance system has been described in detail elsewhere [28].…”
Section: Methodsmentioning
confidence: 99%
“…This particle deceleration is also supported by simulations of impinging jets [33,37]. In order to characterise the impacts of the particle before, during and after impact onto the surface of an electrode, a high-speed electrochemical impedance technique was employed [28]. Here an AC perturbation was applied to the electrode and the current response monitored as a function of time while the jet, containing, sand particles, was directed at the electrode surface.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…Although useful this does not give any other information on the event that caused the erosion itself. To circumvent this limitation, a technique based on high-speed impedance [16,17] analysis has been developed [13,18]. In this case, the uncompensated resistance and the effective capacitance of the electrode (through the measurement of the electrode impedance), was acquired with a 2 µs resolution throughout either cavitation erosion (via bubble dynamics) or sand particle impact [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the uncompensated resistance and the effective capacitance of the electrode (through the measurement of the electrode impedance), was acquired with a 2 µs resolution throughout either cavitation erosion (via bubble dynamics) or sand particle impact [13]. These studies showed that in the former case, bubble growth and collapse preceded the erosion/corrosion event [18] while in the latter case particle approach and impact as well as tumbling [13] could be detected prior to the erosion/corrosion process. These observations are powerful in that the full mechanism can be probed rather than just the aftereffects on their own.…”
Section: Introductionmentioning
confidence: 99%